Deception jamming against anti-ship missiles which use doppler beam sharpening modes - Frazer, Gareth (Cranfield University, 2020)
Missile seekers are becoming increasingly more capable of using Doppler Beam Sharpening (DBS) modes as part of the homing cycle, which requires new countermeasures against this mode. One type of countermeasure, is to create false targets within the seeker DBS image. This thesis presents two implementation methods to insert false targets into DBS images. Both methods are used to create false targets at a precise location within a seeker DBS image, but are implemented in different ways. The first method proposes repeat jamming with a time-varying delay, whilst the second proposes a fixed delay and adding a specific Doppler shift to received waveforms. The effects of tracking errors on the position of the false target are analysed, both analytically and with simulations and used to assess the practical implementation of the jamming scheme. An experimental DBS system was built to test the effectiveness of the jamming scheme against a platform moving in steps and assess errors caused by incorrectly estimating the seeker trajectory. The overall result of the thesis is that using the derived jamming methods, false targets can be created at specific locations in the DBS image of the victim radar, providing the trajectory of the victim radar is known.